Improved Surface Passivation of Rear SiNx/AlOx Stacks in p‐Type Boron‐Doped Czochralski Silicon Wafers During Dark Annealing at Elevated Temperatures. Issue 22 (23rd September 2022) - Hu, Zechen; Lin, Dehang; Zhao, Tong; Hang, Pengjie; Yao, Yuxin; Yu, Xuegong; Yang, Deren
Abstract : Herein, the surface passivation quality of p‐type boron‐doped Czochralski silicon (Cz‐Si) wafers with passivated emitter and rear cell (PERC) structure during 200 °C dark annealing is investigated. During such a treatment, a reduction in the saturation current density ( J 0 ) along with the degradation and regeneration of minority carrier lifetime can only be observed in PERC‐structured wafers that fast fired at high temperatures instead of in unfired wafers, which is possibly correlated with hydrogen injected into the silicon bulk during fast firing. Besides, no notable variations in J 0 can be observed in fast‐fired SiN x / n  + / p ‐Si/ n  + /SiN x symmetrical structure wafers during the same treatment, although their minority carrier lifetime undergoes degradation and regeneration cycles, demonstrating that the improved surface passivation comes from the rear surface of PERC structure. The capacitance–voltage measurement on the fabricated rear surface samples with metal‐insulator‐semiconductor (MIS) structure further demonstrates that the improved surface passivation is not related to field‐effect passivation. By comparing the surface state density of rear surface during dark annealing, it can be concluded that the improved rear surface passivation originates from the hydrogenation of surface defects such as dangling bonds, possibly by the outdiffused hydrogen from silicon bulk during such a treatment. Abstract : In this study, an improved surface passivation in p‐type boron‐doped Czochralski silicon wafers with passivated emitter and rear cell structure, along with the degradation and regeneration of minority carrier lifetime during 200 °C dark annealing, is observed, which is demonstrated to be related to the passivation of rear surface state density by outdiffused hydrogen during such a treatment.